Editorial (Journal of Forest and Livelihood, 2003)
The third Issue of Journal of Forest and Livelihood 2 (2) is now at your hand. You will find an interesting breadth and depth of current policy and institutional landscape in Nepal's forestry sector. The 10 articles of varying lengths link current realities with on-going theoretical and policy debates in the respective sectors. Key issues dealt with include: current forest policy discourse including devolution and micro-macro linkages (monitoring), multistakeholder initiatives in Terai forest management, leasehold forestry contribution to the livelihood of the poor, factors determining poor's access to benefits from community forestry, and a survey of policy-induced problems (forest inventory). In addition, short commentaries on FECOFUN as a civil society, and limitation of protected area model of conservation in times of crisis are also presented.